Leveraging Employer Practices in Global Regulatory Frameworks to Improve Employment Outcomes for People with Disabilities - Saleh, Matthew C. (Social Inclusion, 2018)
Work is an important part of life, providing both economic security and a forum to contribute one’s talents and skills to society, thereby anchoring the individual in a social role. However, access to work is not equally available to people with disabilities globally. Regulatory environments that prohibit discrimination and support vocational training and educational opportunities constitute a critical first step toward economic independence. However, they have not proven sufficient in themselves. In this article, we aim to infuse deeper consideration of employer practice and demand-side policy reforms into global policy discussions of the right to work for people with disabilities. We begin by documenting the employment and economic disparities existing for people with disabilities globally, followed by a description of the international, regional, and local regulatory contexts aiming to improve labor market outcomes for people with disabilities. Next, we examine how policies can leverage employer interests to further address inequalities. We discuss employer policies and practices demonstrated in the research to facilitate recruitment, hiring, career development, retention, and meaningful workplace inclusion. The goal of the article is to synthesize existing international literature on employment rights for people with disabilities with the employer perspective.